Multi-Causal Predictors of Academic Performance Among Senior Secondary School Students: Peer Influence, Social Network Use, and Gender - Habeeb Omoponle Adewuyi (Indonesia Approach Education, 2024)
The study investigated the causal relationship between peer influence, social network usage, gender, and academic performance of senior secondary school students. A descriptive survey research design was used for the study. Both the independent and dependent variables were measured with standardized instruments, which included peer influence factor scale (α = .81), social network questionnaire (α = .78) and student achievement scale (α = .83). The result showed that academic performance has a significant relationship with all the independent variables when put together, with the value of R adjusted = .626 and R2 adjusted = .386; the analysis of variance yielded an F ratio value of 63.62 at 0.05 significant level. In terms of the magnitude of contributions, peer influence made the most with (beta = .554, t = 11.772, p<0.05) followed by social network usage (beta = .168, t = 3.562, p<0.05), while gender had no significant contribution (beta = -.094, t = -2.064, p>0.05). Therefore, it is advised that parents, guardians, and other interested parties be made aware of the consequences of uncultured use of social media among peers and that students be encouraged to make effective and efficient use of their time, especially their free time.